Early identification and monitoring of hidden debris flow in low mountain red bed area based on InSAR and optical remote sensing technology——A case study of Wenjiagou debris flow in the Eastern New District of Chengdu. Issue 6 (October 2021) - Jia, Zhihong; Huang, Xichao; Wang, Qingfang; Yu, Tianbin; Wang, Meng; Jiang, Yu; Song, Ban; Dong, Jihong
Abstract: Because of the typical geological environment and climate conditions, the number of debris flow geological disasters in low mountain red bed area is small, and most of them have high concealment. Identifying and monitoring debris flow under this kind of special disaster pregnant background has a certain significance for the prevention and control of geological disasters. Taking Wenjiagou debris flow in Danjing street, Eastern New District of Chengdu as an example, this paper uses InSAR technology and optical remote sensing technology to identify and monitor Wenjiagou debris flow by multi-period, multi-source and multi-means method. Combined with the geological environment conditions of red bed area, this paper comprehensively analyzes the causes and development characteristics of Wenjiagou debris flow. Research shows:1) The debris flow in Wenjiagou is very hidden. The source of landslide in the early stage can be detected by using InSAR technology, which has certain deformation characteristics. 2) Using multi- period optical remote sensing images, the partial slope deformation can be identified in the study area, and the debris flow can be effectively identified in the early stage. 3) The provenance of Wenjiagou debris flow is mainly controlled by geological structure and stratum lithology. Finally, combined with the results of remote sensing interpretation and ground survey, the paper puts forward the targeted prevention and control suggestions of "Stable material source + Combination of blocking and drainage + Ecological restoration" for Wenjiagou debris flow, which has a certain guiding role for the development and planning of the Eastern New District of Chengdu.